(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: The palmarislongus is a superficial forearm flexor with marked variability in its presence and morphology. Its long, accessible tendon is commonly harvested for reconstructive procedures, making population-specific anatomical data clinically relevant. Aims: To determine the prevalence of absence and morphological variants of the palmarislongus, quantify muscle-belly and tendon dimensions, and compare measurements between sides in cadaveric upper limbs from north-western Rajasthan. Materials and Methods:During the cadaveric dissections at the Department of Anatomy, Government Medical College Nagaur, we studied fifty upper-limb (25 right and 25 left). The muscle was categorized as normal, fleshy, reversed, or absent. Length, width, and thickness of the muscle belly and tendon were recorded. Data were summarized as number, percentage, and mean ± standard deviation; group and side-wise comparisons were performed using appropriate tests, with p<0.05consideredsignificant. Results: The palmarislongus was present in 47 of 50 specimens (94.0%) and absent in 3 (6.0%). Among present muscles, 40 (85.1%) had normal morphology, 4 (8.5%) were fleshy variants, and 3 (6.4%) were reversed variants. Tendon width differed significantly among morphological types (p=0.03), being greatest in the fleshy variant. Other muscle-belly and tendon measurements were comparable across types. No significant side-to-side difference was observed in any morphometric parameter. Conclusion: The palmarislongus was present in most specimens from north-western Rajasthan, although clinically important fleshy and reversed variants were identified. Morphological assessment before tendon harvest may improve operative planning and reduce avoidable neurovascular injury.